2020
DOI: 10.1007/s11547-020-01256-1
|View full text |Cite|
|
Sign up to set email alerts
|

Chest CT for early detection and management of coronavirus disease (COVID-19): a report of 314 patients admitted to Emergency Department with suspected pneumonia

Abstract: Purpose The purpose of our study was to assess the potential role of chest CT in the early detection of COVID-19 pneumonia and to explore its role in patient management in an adult Italian population admitted to the Emergency Department. Methods Three hundred and fourteen patients presented with clinically suspected COVID-19, from March 3 to 23, 2020, were evaluated with PaO2/FIO2 ratio from arterial blood gas, RT-PCR assay from nasopharyngeal swab sample and chest CT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
2
28
0
2
Order By: Relevance
“…Chest CT scans are useful in finding milder patients with pneumonia. 12 In countries with more CT scans, patients with pneumonia © 2021 Tottori University Medical Press can be found earlier, which may lead to lower mortality due to earlier initiation of treatment in patients who become more severe if treatment is delayed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest CT scans are useful in finding milder patients with pneumonia. 12 In countries with more CT scans, patients with pneumonia © 2021 Tottori University Medical Press can be found earlier, which may lead to lower mortality due to earlier initiation of treatment in patients who become more severe if treatment is delayed.…”
Section: Discussionmentioning
confidence: 99%
“…11 We also considered the number of CT scans, as a paper suggests that CT scans can lead to earlier detection of pneumonia caused by COVID-19. 12 We used ecologic studies to evaluate these candidate factors.…”
mentioning
confidence: 99%
“…Warren et al 44 have demonstrated, in acute respiratory distress syndrome (ARDS), that a higher CXR severity score was independently associated with a lower P/F ratio and a worse survival. In Covid-19 patients, a significant correlation was found between CT findings and P/F ratio 45 and Pan et al 46 showed that SpO2 ≤ 89% was an independent risk factor of death.…”
Section: Discussionmentioning
confidence: 93%
“…5,10 Over the last few months, a huge amount of papers concerning diagnostic and prognostic value of imaging of COVID-19 has been published. [11][12][13][14][15][16][17][18][19][20][21] This proves that radiology research has not stopped during COVID-19 pandemic and that this emergency has become a main topic of several trials and research activities. Nevertheless, the impact of COVID-19 outbreak on radiology research has been scarcely considered.…”
Section: Introductionmentioning
confidence: 90%